The Impact of Institutional Quality on Tax Revenue in Developing Countries - Phuong, Lien Nguyen (Asian Journal of Empirical Research, 2015)
This article applies the method of difference panel GMM Arellano-Bond for a dataset of eighty two developing countries (These countries are classified into three economies basing on estimates of gross national income (GNI) per capita for the 2014 year by using the World Bank Atlas method ) during a period from 1996 to 2013 to empirically assess the impact of institutional quality (based on six World Bank governance indicators ) on government tax revenue. The results show a significantly positive impact of institutional quality on tax revenue in the whole sample, as well as in the low-income and lower-middle income groups while this impact is significantly negative in upper-middle income group. These results are definitely consistent and robust for all six World Bank governance indicators. The findings suggest governments in developing countries should appropriately adjust institutional quality to improve the tax revenue and promote economic activities.